Identification and characterization of a novel aminoglycoside O-nucleotidyltransferase ANT(6)-If from Paenibacillus thiaminolyticus PATH554 - Lu, Junwan; Sha, Yuning; Gao, Mengdi; Shi, Weina; Lin, Xi; Li, Kewei; Bao, Qiyu; Feng, Chunlin (Frontiers in Microbiology, 2023)
Background: Paenibacillus thiaminolyticus, a species of genus Paenibacillus of the family Paenibacillaceae, exists widely in environments and habitats in various plants and worms, and occasionally causes human infections. This work aimed to characterize the function of a novel aminoglycoside O-nucleotidyltransferase resistance gene, designated ant(6)-If, from a P. thiaminolyticus strain PATH554. Methods: Molecular cloning, antimicrobial susceptibility testing, enzyme expression and purification, and kinetic analysis were used to validate the function of the novel gene. Whole-genome sequencing and comparative genomic analysis were performed to investigate the phylogenetic relationship of ANT(6)-If and other aminoglycoside O-nucleotidyltransferases, and the synteny of ant(6)-If related sequences. Results: The recombinant with the cloned ant(6)-If gene (pMD19-ant(6)-If/DH5α) demonstrated a 128-fold increase of minimum inhibitory concentration level against streptomycin, compared with the control strains (DH5α and pMD19/DH5α). The kinetic parameter kcat/Km of ANT(6)-If for streptomycin was 9.01×103 M−1·s−1. Among the function-characterized resistance genes, ANT(6)-If shared the highest amino acid sequence identity of 75.35% with AadK. The ant(6)-If gene was located within a relatively conserved genomic region in the chromosome. Conclusion: ant(6)-If conferred resistance to streptomycin. The study of a novel resistance gene in an unusual environmental bacterium in this work contributed to elucidating the resistance mechanisms in the microorganisms.